Kegiatan Donor Darah dalam Aksi Donor Pastor dan Jemaat Gereja Katolik Kabanjahe Bekerjasama dengan Unit Donor Darah Palang Merah Indonesia Kabupaten Karo - Daniel Ginting; Nina Fentiana (Lembaga Pengembangan Kinerja Dosen, 2025)
Blood donation activities are carried out to maintain the stability of the blood stock of the Karo Regency PMI. Blood donation activities are carried out on Monday, December 22, 2024 starting at 09.00 WIB at the Kabanjahe Catholic Church. The blood donation service activity was attended by a total of 28 participants. From the results of the implementation of the activity, 26 blood bags have been collected. Based on interviews with the participants, their motivation to donate blood is because of a sense of humanity for people in need, to maintain their health, invitations from friends, and some are interested because of the gifts offered at the end of the event. The implementation of this blood donation activity as a form of community service has been carried out well and has received a good response from the participants. Socialization is also needed so that the number of blood donors increases and more people are willing to become blood donors.